2018
DOI: 10.1002/jcb.27161
|View full text |Cite
|
Sign up to set email alerts
|

SPDEF is overexpressed in gastric cancer and triggers cell proliferation by forming a positive regulation loop with FoxM1

Abstract: The SAM-pointed domain-containing ETS transcription factor (SPDEF) is an epithelial-specific transcription factor of the E26 transformation-specific (ETS) family, which binds the target gene through the high-affinity sequence of GGAT. It is suggested that SPDEF targets the promoter activity of Forkhead Box M1 (FoxM1), which has been proven to be highly expressed in gastric cancer. We found that SPDEF was overexpressed both at the messenger RNA (mRNA) and at the protein level in human gastric cancer species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…SPDEF targets FoxM1 (Forkhead Box M1) promoter activity, which has been proven to be highly expressed in gastric cancer. Wu and colleagues found that SPDEF was overexpressed at the mRNA and protein level in human gastric cancer species [15].…”
Section: Spdef (Sam Pointed Domain Containing Ets Transcription Factomentioning
confidence: 99%
“…SPDEF targets FoxM1 (Forkhead Box M1) promoter activity, which has been proven to be highly expressed in gastric cancer. Wu and colleagues found that SPDEF was overexpressed at the mRNA and protein level in human gastric cancer species [15].…”
Section: Spdef (Sam Pointed Domain Containing Ets Transcription Factomentioning
confidence: 99%
“…5 Recent evidence has highlighted the crucial roles of TFs in manipulating GC cells proliferation. 6,7 For example, the TEA domain family member 4 (TEAD4), a component of Hippo signaling pathway, was highly expressed in GC tissues and positively associated with poor outcomes in GC patients. Knockdown of TEAD4 significantly decreased the growth of GC cells both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, ETS1 could regulate cell viability via interfering glycolysis in pancreatic cancer ( 86 ); increased expression of ETS2 promotes drug resistance in colorectal cancer ( 87 ). Interestingly, unlike its tumor-suppressive role in colorectal cancer and HCC, PDEF is overexpressed in gastric cancer and promotes gastric cancer cell proliferation by regulating FoxM1 expression through a positive feedback loop ( 39 , 88 , 89 ). In conclusion, ETS family may offer vast potential for developing novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%